Errata and retractions associated with research papers published by authors with Hungarian affiliations - da Silva, Jaime A Teixeira (Pensoft Publishers, 2021)
Background: To examine the errata and retractions in total published output of Hungarian research and academia relative to that in 34 other European countries. Objective: To analyse the number of errata and retractions related to papers published by authors with Hungarian affiliations compared to those by authors with affiliations in the 34 other countries. Methods: Errata and retractions retrieved from three databases, namely Retraction Watch, Web of Science (WoS), and Scopus, were counted and sorted by country. Results: Scopus featured 7 retractions linked to Hungarian affiliations and WoS featured 10. Retraction Watch featured 26 such retractions, placing Hungary in 23rd position among the 35 countries arranged in descending order of the number of retractions. Of the 26 retractions from Hungary, 5 were in Elsevier journals and another 5 in Springer Nature; also, 8 of the 26 were associated with the University of Debrecen. When ranked for the number of errata notices for every 1000 published papers, Hungary was ranked 29th in WoS (2.54 notices per 1000 papers) and 26th in Scopus (2.3 notices per 1000 papers). Conclusions: The low numbers of Hungarian affiliations suggest that either research ethics are more stringently observed in Hungary or that publications from Hungarian research institutes, including papers in Hungarian – many Hungarian journals are indexed neither in WoS nor in Scopus – have not been scrutinized adequately through post-publication peer review. © 2021, Pensoft Publishers. All rights reserved.